Variations of technical actions and efficacy of national teams' volleyball attackers according to their sex and playing positions. (4th July 2019) - Lima, Ricardo; Palao, José M.; Moreira, Miguel; Clemente, Filipe Manuel
ABSTRACT: The purpose of this study was to analyse the variations of technical actions and efficacy of national teams' volleyball players according to their sex and playing positions. The study included 8, 541 rallies played in 74 volleyball matches (37 matches for each sex, 2018 European Volleyball Golden League). The variables studied were: sex (male or female), player role (outside-hitter, middle-blocker, and opposite), points scored by the attackers, errors done by the attackers, points obtained by the attackers in the side-out phase (or break-point phase), serves executed, serve efficacy (error, continuity, and aces), receptions, reception efficacy (errors, positive, and perfect), attack executed, attack efficacy (errors and points), and block executed. The results revealed difference between male and female players in the execution of the serve and the attack. Male players assume higher risk at serve, and they had higher attack efficacy than female players. Male opposite players have a higher contribution and efficacy on attack than female opposite players. Female middle blockers and outside-hitters had a higher participation in attack. The results revealed difference between male and female players in the execution of the serve and the attack. Male players assume higher risk at serve, and they had higher attack efficacy than female players. Male opposite players have a higher contribution and efficacy on attack than female opposite players. Female middle blockers and outside-hitters had a higher participation in attack.